Silk threads back a long way - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Gareth Davies writes from Waterloo in Belgium in response to the article inspired by ICIPE on 'Silk route now through Africa' in Spore 92. 'The manufacture of local silk and its use in garment making in Africa does predate ICIPE. There used to...